The main areas of state regulation of the improvement of legal consciousness and the culture of citizens - Zhumagulov Т.Б.; Daribayev Ғ.С. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The formation of the legal consciousness and culture of citizens in accordance with the requirements of modern society is one of the main priorities of the state. This has resulted from ignorance of the laws adopted by the state, misunderstanding of their rights and obligations defined by law, and disrespect for the law among citizens can lead to legal nihilism and various criminal and administrative offenses. This requires a revision of the legal policy of the state, and the issue of raising the legal awareness of citizens. In general, the establishment of peace and order in society is primarily the result of a positive attitude of the members of this society to the law. The higher the legal awareness, the lower the dynamics of crime in society and the stronger the system of law and order in the state. Therefore, defining the essence of the concepts of legal consciousness and legal culture, one of the most pressing issues today is to determine the effectiveness of the system of state measures to improve the legal awareness of citizens in the country and analyze the results.